How successful are International Monetary Fund loan programs? - HAJARNAVIS, Kavish; MAHAJAN , Dhruv; ROH, Hyunwoo (Journal of Economics Library, 2023)
Abstract. This paper evaluates the effectiveness of International Monetary Fund (IMF) loan programs from 2000 to 2010 by looking at macroeconomic indicators such as the unemployment rate, inflation, real GDP, government debt as a percentage of GDP, and export value. Data is used from the year before the implementation of the IMF loan program to three years after the loan policy was implemented. We chose three years into the future because it gives time for the macroeconomic factors within a country to fully materialize while weeding out much “white noise” (shocks that have nothing to do with the program itself). Our analysis shows that IMF loan programs between 2000 and 2010 were generally unsuccessful in improving macroeconomic growth and stability in countries that sought loans. An accompanying workbook contains the data. Keywords. IMF; Lending. JEL. F30; F33; F34.